PTU-024 Endoscopic Cholecystogastrostomy in a Patient with Gallbladder Empyema Secondary to Cholangiocarcinoma. (17th August 2016) - Paranandi, B; Nayar, MK; Scott, J; Charnley, RM; Wilson, C; Oppong, KW
Abstract : Introduction: In cases of obstruction of the gallbladder (GB) or cystic duct where surgery is high risk, EUS guided GB drainage (EUS-GBD) is reported to have comparable efficacy to percutaneous drainage. 1 However, the technique has not been widely adopted due to lack of specific devices and concerns about leakage and stent migration. Lumen apposing metal stents (LAMS) have been developed to minimise the risk and simplify the procedure. A novel (Hot AXIOS™) device has recently become available and this consists of a stent and electrocautery-enhanced delivery system, enabling a single device to be used when previously multiple devices and steps were required. There is a single case report of its use for EUS-GBD in the literature. 2 A 68 year-old female, presented with obstructive jaundice, due to inoperable hilar cholangiocarcinoma. A Percutaneous transhepatic cholangiography (PTC) procedure was performed and an internal external drain placed. Shortly afterwards she developed clinical features of cholecystitis. A CT scan showed gross distension of the GB and a GB stone. There was extensive pericholecystic fluid with fat stranding. Following HPB MDT discussion, a decision was made to perform EUS-GBD using a Hot AXIOS™. Methods: The procedure was undertaken under conscious sedation, using a therapeutic echoendoscope. The optimal site for access was identified as being in the antrum. The GB was punctured with the Hot-AXIOS device (15 mm x 10 mm (W x L) 24 mm flange diameter stent) and a cutting current was applied. X-ray screening was used; however, deployment was entirely under EUS control. The stent was dilated with a 10 mm balloon. Results: The procedure was well tolerated and completed within 15 minutes. The stent was in a good position on EUS and fluoroscopy. A large amount of pus drained immediately. There was a rapid improvement in clinical condition and inflammatory markers over the next few days. Biliary drainage was internalised with placement of 2 metal stents. CT scans 8 days and 7 weeks post placement showed the stent in a good position with resolution of the cholecystitis. Conclusion: Technical and clinical success was achieved in this case which to the best of our knowledge is the first EUS-GBD procedure in the UK utilising this device. Further experience of EUS-GBD with the Hot AXIOS™ and randomised controlled trials against percutaneous drainage are required to delineate its role in high risk surgical cases. References: 1 Jang JW, et al. Gastroenterol . 2012 Apr;142 (4):805–11. 2 Teoh AYB, et al. GIE 2014;80 (6):1171. Disclosure of Interest: None Declared